2002
DOI: 10.1046/j.1365-2133.2002.04640.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nicotinic receptors in the skin of patients with palmoplantar pustulosis

Abstract: Smoking can influence nAChR expression. The altered nAChR staining pattern in PPP skin may indicate a possible role for nicotine in the pathogenesis of PPP. We hypothesize that there is an abnormal response to nicotine in patients with PPP, resulting in inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 14 publications
(24 reference statements)
5
79
0
4
Order By: Relevance
“…This exclusive role of muscarinic receptors in nicotinic sweating is in contrast to nicotinic cutaneous vasodilation wherein there is a muscarinic-insensitive component of nicotinic cutaneous vasodilation (see above). This difference may infer that nicotinic receptors located on sweat glands (Hagforsen et al 2002) do not functionally modulate sweating whereas those on skin vessels (Hagforsen et al 2002) modulate cutaneous vasodilation.…”
Section: Mechanisms Of Nicotinic Skin Vasodilation and Sweating 19mentioning
confidence: 99%
See 2 more Smart Citations
“…This exclusive role of muscarinic receptors in nicotinic sweating is in contrast to nicotinic cutaneous vasodilation wherein there is a muscarinic-insensitive component of nicotinic cutaneous vasodilation (see above). This difference may infer that nicotinic receptors located on sweat glands (Hagforsen et al 2002) do not functionally modulate sweating whereas those on skin vessels (Hagforsen et al 2002) modulate cutaneous vasodilation.…”
Section: Mechanisms Of Nicotinic Skin Vasodilation and Sweating 19mentioning
confidence: 99%
“…It is likely that the nicotine infusion activated nicotinic receptors located on endothelial cells of the cutaneous blood vessels (Hagforsen et al 2002), which subsequently activated COX also located in the endothelial cells (Muller-Decker et al 1999). The activation of COX by nicotine may increase superoxide production from COX itself (Egan et al 1976), or NADPH oxidase (Zhang et al 2011).…”
Section: Cutaneous Vasodilationmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Furthermore, nicotinic receptors expression is altered in the epidermis of patients with PPP, and nicotine would lead to an inflammatory response with altered expression of acetylcholinesterase (acetylcholine degrading enzyme), resulting in lesions of PPP. 70 The triggering mechanism of inflammation is unknown. 71 Contactants may play a role in the etiopathogenesis of PPP, although the prevalence of positive patch tests varies.…”
Section: Palmoplantar Pustulosismentioning
confidence: 99%
“…69 Sudoresis and the glandular apparatus appear to play an important role in the pathogenesis of PPP. 70 Some studies have shown the presence of an abnormal portion of the acrosyringium in the epidermis of patients with PPP, suggesting its participation in the etiopathogenic process of pustule formation. 60 Furthermore, nicotinic receptors expression is altered in the epidermis of patients with PPP, and nicotine would lead to an inflammatory response with altered expression of acetylcholinesterase (acetylcholine degrading enzyme), resulting in lesions of PPP.…”
Section: Palmoplantar Pustulosismentioning
confidence: 99%